2018
DOI: 10.1371/journal.pone.0208482
|View full text |Cite
|
Sign up to set email alerts
|

Which primary care practitioners have poor human papillomavirus (HPV) knowledge? A step towards informing the development of professional education initiatives

Abstract: BackgroundPrimary care practitioners (PCP) play key roles in cervical cancer prevention. Human papillomavirus (HPV) knowledge is an important influence on PCPs’ cervical cancer prevention-related behaviours. We investigated HPV knowledge, and associated factors, among general practitioners (GPs) and practice nurses.MethodsA survey, including factual questions about HPV infection and vaccination, was mailed to GPs and practice nurses in Ireland. Multivariable logistic regression was used to determine which PCPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In previously conducted studies, the knowledge of health professionals varies depending on age [ 8 ], region [ 9 ], level of education [ 9 ], and the number of years since training [ 10 ]. The relationship between HPV knowledge and pro-vaccine behavior is a problem that has already been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In previously conducted studies, the knowledge of health professionals varies depending on age [ 8 ], region [ 9 ], level of education [ 9 ], and the number of years since training [ 10 ]. The relationship between HPV knowledge and pro-vaccine behavior is a problem that has already been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Although up to 88% of GPs report confidence in explaining the safety and efficacy of HPV vaccination ( Chauvet, 2016 ; Pelissier and Bastides, 2008 ; Raude et al, 2016 ; Tutala, 2019 ; Verger et al, 2015 ), the percentage of GPs who will be able to answer related specific questions is probably much lower, as reported in France and in other settings ( Tutala, 2019 ; McSherry et al, 2018 ). This result together with the fact that up to 50% of GPs reports doubts and concerns regarding HPV vaccination is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…The reported awareness on HPV and associated diseases was high, but the estimated proportion of preventable disease cases by vaccination was clearly underestimated. Various studies have shown vaccination providers’ knowledge gaps [ 14 , 27 , 28 ], and insufficient knowledge on HPV and the HPVv has been identified as a personal barrier to providing the HPVv [ 25 ]. Furthermore, it became apparent among the survey respondents that patient age and gender strongly influence their attitudes.…”
Section: Discussionmentioning
confidence: 99%